Adapting participatory processes in temporary rivers management. Issue 120 (June 2021) - Soria, Maria; Bonada, Núria; Ballester, Alba; Verkaik, Iraima; Jordà-Capdevila, Dídac; Solà, Carolina; Munné, Antoni; Jiménez-Argudo, Sara-María; Fortuño, Pau; Gallart, Francesc; Vinyoles, Dolors; Llorens, Pilar; et al.
Highlights: Participatory processes are key in river management but remain scarce in temporary rivers. Despite their ecological importance, temporary rivers are socially considered in low esteem. Raising awareness on temporary rivers is key to increase stakeholders' engagement. Involving stakeholders also in the diagnosis of rivers increased their knowledge. Our approach can contribute to adapt current participatory processes to future management needs. Abstract: The European Water Framework Directive (WFD) mandates to incorporate the participation of stakeholders and the general public in the development and updating of the river basin management plans. So far, the WFD implementation has been mainly focused on perennial rivers without considering temporary rivers properly, neither in biomonitoring programs nor participatory processes. This paper aims at adapting participatory processes in river basin management to enhance the inclusion of ecosystems with poor or no social recognition such as temporary rivers. To do so, we examined previous experiences of participatory processes conducted in the WFD and adapted them to propose and implement an approach for promoting stakeholders' engagement in temporary rivers. The approach is based on a collaborative leadership, includes multiple participatory engagement mechanisms, uses future global change scenarios and the concept of ecosystem services at different stages of the process, and aims at involving stakeholders not only in the proposal of measures stage but in the diagnosis of the ecological status. It also includes an evaluation of participants' satisfaction on the process. We tested our approach in temporary rivers from the Mediterranean region. We found that the combination of environmental education and citizen science activities, together with the inclusion of the ecosystem services concept, was the most useful way to raise awareness on the biodiversity and ecological value of temporary rivers and to promote stakeholders' engagement. Workshops conducted during the diagnosis stage played an important role in both including stakeholders' suggestions and increasing their knowledge on temporary rivers. Further, envisaging climate-related future scenarios allowed participants to incorporate measures that could tackle new and emerging pressures on these ecosystems. As future environmental changes will increase the proportion of rivers with temporary flow regimes, our approach can contribute to adapt current participatory processes to future needs.